PRELIMINARY STUDY ON GENETIC VARIATION OF Sudanonautes africanus IN SOUTH-WEST, NIGERIA USING SDS-PAGE TECHNIQUE - POPOOLA, O. M; UDOH, F. E. (Nigerian Journal of Fisheries, 2020)
Freshwater crabs are a cheap and important source of animal protein for human beings. They also serve as bio indicators of ecosystem disruption and also conservation icons. Despite their importance, there are still some unresolved issues in their phylogenies. This study is to observe the genetic variations in one of the species of freshwater crab, S. africanus from three different water bodies in South-west, Nigeria using Sodium Dodecyl Sulfate Polyacrylamide (SDS-PAGE) gel electrophoresis. Muscle protein was extracted from the individual crab in each of the population. The molecular weights of protein bands were observed and its ranges were 13.20 – 214.80kDa, 11.60 – 193.40kDa in Ogbese River and 19.30 – 193.40kDa in Owena River populations. UPGMA dendrogram formed to show the genetic similarities of the populations revealed two major clades. The study shows that there are intra and inter-population variations in each of the study locations.